An approach towards a sustainable urban city - utilization of existing rooftop solar energy panels by making use of DC appliances - Rifat, Ashir Hamim; Hossain, Muckbul; Islam, Rifatul; Noman, Shoud (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2021.